O efeito do material concreto e do modelo de barras no processo de aprendizagem significativa do conteúdo curricular de frações pelos alunos de 7º ano do ensino fundamental - Gois, Renata Cláudia (Universidade Federal de São Carlos, 2014)
The dissertation presents a proposal for teaching the content of fractions to a 7th grade classroom of basic education, based on a concrete didactical material, Fraction Case , and the Bar Model inspired in Singapore Mathematics, focused on the conceptual understanding along with basic operation skills. The motivation to this work was the recognition of great difficulty in learning with understanding of rational numbers, shown by the students of basic education across the grades. The learning of rational numbers is of fundamental importance to the accomplishment of the mathematics curriculum of basic education. We adopted the Fraction Case and the Bar Model because they actually offer the possibility of visualizing concrete representation of ideas that underline the subject of fractions. The proposed activities were inspired by the didactical ideas and activities in Baldin & Malagutti (2006), and they aim at the understanding of the concept of equivalent fractions together with the basic operations of addition, subtraction, multiplication and division of fractions, starting from the perspective of the part-whole relationship. We bring out the outcome resulted from the application of activities in three classrooms of 7th grade students of a private school of city of Bauru.
Keywords: Frações; Aprendizagem significativa; Material concreto; Modelo de barras; Meaningful learning; Fractions; Concrete didactical material; Bar model; CIENCIAS EXATAS E DA TERRA